2008
DOI: 10.1016/j.jtcvs.2007.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Growing clinical evidence for the interaction of the p53 genotype and response to induction chemotherapy in advanced non–small cell lung cancer

Abstract: This is the second clinical evaluation demonstrating a significant relation between p53 genotype and response to induction therapy in non-small cell lung cancer. We conclude that the p53 genotype should be evaluated as a predictive marker for response to induction therapy in prospective randomized protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
(30 reference statements)
2
28
0
1
Order By: Relevance
“…34,35 Interestingly, TP53 mutations have been found to be associated with resistance to cisplatin combined with etoposide 36 in nonsmall cell lung cancer as well as to cisplatin combined with ifosfamide. 37 The results from the former study 36 may be consistent with the observations regarding anthracyclines in as much as etoposide, being a Topo-II inhibitor, resembles the anthracyclines with respect to mechanism of action. Ifosfamide, on the contrary, is metabolized into cyclophosphamide in vivo.…”
Section: Tp53supporting
confidence: 82%
“…34,35 Interestingly, TP53 mutations have been found to be associated with resistance to cisplatin combined with etoposide 36 in nonsmall cell lung cancer as well as to cisplatin combined with ifosfamide. 37 The results from the former study 36 may be consistent with the observations regarding anthracyclines in as much as etoposide, being a Topo-II inhibitor, resembles the anthracyclines with respect to mechanism of action. Ifosfamide, on the contrary, is metabolized into cyclophosphamide in vivo.…”
Section: Tp53supporting
confidence: 82%
“…Previous studies have investigated whether TP53 mutations are of prognostic value in predicting response to chemotherapy in NSCLC; the results are controversial (41). In a 35-patient study, the presence of mutant TP53 was highly indicative of resistance to cisplatin (P ¼ 0.002) (42), while in a study involving 253 patients, TP53-positive patients had a significantly greater survival benefit from adjuvant chemotherapy compared with TP53-negative patients (43). Another report in the International Adjuvant Lung Cancer Trial (IALT), a randomized trial of adjuvant cisplatin-based chemotherapy, found no correlation between TP53 mutation and outcome in 524 patients (44).…”
Section: Discussionmentioning
confidence: 99%
“…To date, dysfunction of tumor suppressor genes has been confirmed as the most significant genetic damage in human cancers. Mutations or deletions of p53 occur in 50-70% of non-small cell lung cancers (NSCLCs) and are associated with poor prognosis of lung cancer patients (3,4).…”
Section: Introductionmentioning
confidence: 99%